Solar-powered seaweed powder milling: enhancing value in the blue economy - Nugraha, I Made Aditya; Desnanjaya, I Gusti Made Ngurah; Luthfiani, Febi; Idrus, Muhamad Amril (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
Design and build a seaweed powder milling machine with the blue economy concept is one form of increasing the added value of selling seaweed in Indonesia and utilizing solar energy which is so abundant in Indonesia by using photovoltaic system. This machine is expected to increase the income of seaweed cultivators, and indirectly support the blue economy policy which is one of the policies in Indonesia. Design and build this machine using several supporting components, such as solar panel, battery control unit (BCU), inverter, battery, and motor to drive the seaweed powder milling machine. Testing is carried out by measuring the voltage and current output, and adding environmental conditions. Apart from that, the economics of the machine are also analyzed. Based on the results obtained, the machine can produce electrical energy in the range of 396.95-646 Wh/day, and can operate for up to 131 minutes, with a seaweed flour output of 10-20 kg per hour. From an economic perspective, the payback period is 0.22 years, NPV of IDR 605,286,359.01, with an IRR of 449%. From this value it can be seen that economically the tool is profitable if used by seaweed cultivators.